2017
DOI: 10.1080/02688697.2017.1368449
|View full text |Cite
|
Sign up to set email alerts
|

Two-year experience of multi-disciplinary team (MDT) outcomes for brain metastases in a tertiary neuro-oncology centre

Abstract: Brain metastases (BMs) are the most common intracranial tumour in adults and form a significant proportion of the neuro-oncology workload. Their management has progressed significantly in the last few decades but a gold-standard evidence-based management strategy has not been defined to date and several guidelines based on available evidence exist to support clinical decision-making. This paper evaluates the decision-making process of the neuro-oncology multi-disciplinary team (MDT) in a tertiary neuro-oncolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…We believe that all MRI results should be interpreted in the clinical context (including patient symptoms and clinical findings, date and type of treatment received, and systemic status). This is preferably discussed in a neuro‐oncology multidisciplinary team meeting, which is the optimal place to make decisions regarding further diagnostic work‐up (such as closer follow‐up or stereotactic biopsy) and treatment …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that all MRI results should be interpreted in the clinical context (including patient symptoms and clinical findings, date and type of treatment received, and systemic status). This is preferably discussed in a neuro‐oncology multidisciplinary team meeting, which is the optimal place to make decisions regarding further diagnostic work‐up (such as closer follow‐up or stereotactic biopsy) and treatment …”
Section: Discussionmentioning
confidence: 99%
“…This is preferably discussed in a neuro-oncology multidisciplinary team meeting, which is the optimal place to make decisions regarding further diagnostic work-up (such as closer follow-up or stereotactic biopsy) and treatment. 40,41 In order to validate DSC MR perfusion for clinical application, it is essential to further investigate potential causes of heterogeneity. Ideally, this is done by prospective studies following ASFNR recommendations regarding DSC MR perfusion acquisition and postprocessing.…”
Section: Discussionmentioning
confidence: 99%
“…Two out of three RCTs found a statistically significant longer median survival and better quality of life in the surgical resection group. Two other large RCTs looked at the effect of SRS in combination with WBRT 15,27 in the management of single or multiple CMs and found that a combination of the two treatment modalities may show improved neurological function and intracranial tumor control, however does not show improved median survival. These findings were confirmed by a meta-analysis of 27 RCTs.…”
Section: Pattern Of CM Referralsmentioning
confidence: 99%
“…Another reason could be that more surgery is offered to the elderly as an increasing number of otherwise fit patients are referred in an ageing population. 27 There have been efforts to develop new stratification tools such as the Barnholtz-Sloan index 46 , Score Index for Radiosurgery (SIR) and Basic Score for Brain Metastases (BSBM) amongst others 6,47,48 to guide NMDT decision-making for this heterogeneous cohort of patients. These have not been widely adopted into clinical practice for a number of reasons, presumably due to the fact that most of these scores are based on survival data alone without considering other important factors such as quality of life and tumor recurrence.…”
Section: Validation Of Rpa and Ds-gpamentioning
confidence: 99%
See 1 more Smart Citation